Big Data, Machine Intelligence and Their Impacts to the Future World - Jun Wu (Dianxin kexue)
Big data has become the next frontier for innovation, competition, and productivity since 2008. However, most people still limited their vision on the quantity and the variety of big data, while ignored the crucial role it played in machine intelligence that was taking off recently.Therefore,comprehensive analysis on global and disruptive impacts to the future world due to big data and machine intelligence development was made. It was started from the introduction on development history of machine intelligence. The important role of big data to solve the problem of machine intelligence was analyzed. Combined with the actual case, the meaming of big data and the similarity and differences of big data and large data were investigated.The key techniques of big data and machine intelligence were described.Finally the challenges for futrure world due to machine intelligence development were discussed.